Human Brain Organoids as an In Vitro Model System of Viral Infectious Diseases - Su, Xuan; Yue, Peng; Kong, Jing; Xu, Xin; Zhang, Yu; Cao, Wenjing; Fan, Yuxin; Liu, Meixiao; Chen, Jingjing; Liu, Aihua; Bao, Fukai (Frontiers in Immunology, 2022)
Brain organoids, or brainoids, have shown great promise in the study of central nervous system (CNS) infection. Modeling Zika virus (ZIKV) infection in brain organoids may help elucidate the relationship between ZIKV infection and microcephaly. Brain organoids have been used to study the pathogenesis of SARS-CoV-2, human immunodeficiency virus (HIV), HSV-1, and other viral infections of the CNS. In this review, we summarize the advances in the development of viral infection models in brain organoids and their potential application for exploring mechanisms of viral infections of the CNS and in new drug development. The existing limitations are further discussed and the prospects for the development and application of brain organs are prospected.